PENGARUH GAYA KEPEMIMPINAN, KOMPENSASI DAN LINGKUNGAN KERJA FISIK TERHADAP KINERJA KARYAWAN PADA CV. TRI BHAKTI ADVERTISING BADUNG, BALI - Ni Komang Dila Merliyani; Ni Made Dwi Puspitawati; Gde Bayu Surya Parwita (VALUES, 2024)
The decline in employee performance caused by leadership style, compensation, and work environment has an impact on the target for creating and placing advertisements in 2022, which has not yet been fully realized. The research aims to determine and analyze the influence of leadership style, compensation, and the physical work environment on employee performance at CV. Tri Bhakti Advertising Badung The population of this research is all CV employees. Tri Bhakti Advertising uses a sampling technique using a saturated sampling method where the number of samples is the entire population. So the number of samples in this study was 31. The data collection method used was a questionnaire. The data analysis technique used in this research is multiple linear regression analysis using the SPSS Version 25 test tool. The results of this research show that leadership style, compensation, and the physical work environment have a positive and significant effect on employee performance at CV. Tri Bhakti Advertising Badung For future researchers, it is recommended to use other variables related to employee performance, such as work discipline, competency, job satisfaction, organizational culture, and so on. Future researchers are also advised to use other research locations to obtain different sample sizes and broader research results.